Effects of the Use of Care Bundles in Preventing Ventilator-Associated Pneumonia: An Integrative Literature Review - Maran, Edilaine; Spigolon, Dandara Novakowski; Matsuda, Laura Misue; Teston, Elen Ferraz; Oliveira, João Lucas Campos de; Souza, Verusca Soares de; Marcon, Sonia Silva (Revista Cuidarte, 2020)
Introduction: The ventilator-associated pneumonia is an infection related to health care that predominates in intensive care units and compromises patient safety. Objective: To identify the effects of care bundles in preventing ventilator-associated pneumonia in the Intensive Care Unit (ICU). Materials and Methods: An integrative literature review was conducted based on the studies available in the online databases Cumulative Index to Nursing and Allied Health Literature, Cochrane Library, Latin American and Caribbean Health Sciences Literature, Medical Literature Analysis and Retrieval System Online, Scientific Electronic Library Online and Scopus. Articles were selected from these databases between June 2 and July 18, 2018 in English and Portuguese without any publication time limit using DeCS and MeSh descriptors. Two independent researchers carried out the article selection process, from which information related to publication year, country of origin, objective(s), degree of scientific recommendation and type of study, intervention, compliance with the use of care bundles, main results and conclusions was collected. Results: A total of 13 out of 20 publications analyzed were from different countries and in most studies (n=18) the use of care bundles was found to significantly reduce the incidence of ventilator-associated pneumonia, resulting in a reduction in mortality, length of hospital stay and costs. The main components chosen to put together care bundles included head of bed elevation and oral care. Conclusion: Although studies with a higher degree of recommendation are possible, data from several countries suggest that the use of care bundles had a positive effect on ventilator-associated pneumonia, as well as on improving institutional performance by reducing health care costs.How to cite this article: Maran, Edilaine; Spigolon, Dandara Novakowski;, Matsuda, Laura Misue;  Teston, Elen Ferraz; Oliveira, João Lucas Campos de;  Souza, Verusca Soares de;  Marcon, Sonia Silva.   Efeitos da utilização do bundle na prevenção de pneumonia associada à ventilação mecânica: revisão integrativa Revista Cuidarte. 2021;12(1):e1110. http://dx.doi.org/10.15649/cuidarte.1110
Keywords: Patient Care Bundles; Pneumonia, Ventilator-Associated; Patient Safety; Intensive Care Units